Peran Perawat Ambulans dalam Pelayanan Pre Hospital di Indonesia: Kajian Literatur - Kharisma Adytama Putra; Masfuri Masfuri; Juliana G. E. P. Massie (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Prehospital nurse today are highly needed and perform specialized care. There are high expectations with respect to knowledge and competence of the nurses in prehospital care, as they possess a medical responsibility for emergency patient care in this setting. Nurses are responsible for staffing ambulances in Indonesia. However, those nurses may have limited knowledge and skills in prehospital care because the Indonesian nursing curriculum focuses mostly on in-hospital care. The overall aim of this literature review was to to explore current condition about prehospital care and prehospital nurses’ competence in Indonesia. A search of research literature published from 2000 to 2018 and indexed in CINAHL, EBSCO, ProQuest and Google Scholar was undertaken, and relevant sources were selected to build an informed discussion. Keywords: competence; emergency; nurse; pre hospital ABSTRAK Dewasa ini, perawat pre hospital sangat dibutuhkan dan memiliki keahlian khusus. Harapan tinggi diberikan masyarakat pada perawat pre hospital berkaitan dengan tingkat pengetahuan dan kompetensi perawat dalam pemberian asuhan keperawatan kegawat daruratan di area pre hospital. Perawat pre hospital bertanggung jawab terhadap tata kelola ambulans di Indonesia. Namun, perawat pre hospital masih memiliki pengetahuan dan ketrampilan yang terbatas dalam tatalaksana asuhan pre hospital. Oleh karena kurikulum keperawatan Indonesia sebagian besar hanya berfokus pada perawatan intra Rumah Sakit. Tujuan dari tinjauan literatur ini adalah untuk mengeksplorasi kondisi saat ini tentang perawatan pra-rumah sakit dan kompetensi perawat pra-rumah sakit di Indonesia. Metode penulisan artikel ini menggunakan penelusuran literatur melalui database online seperti CINAHL, EBSCO, ProQuest dan Google Scholar. Literatur diberi batasan dari tahun 2000 – 2018. Kata kunci: gawat darurat; kompetensi; perawat; prehospital